2013
DOI: 10.2147/ndt.s47879
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia for differentiating Alzheimer’s disease from subcortical vascular dementia and mild cognitive impairment

Abstract: Although ideomotor limb apraxia is considered to be a typical sign of cortical pathologies such as Alzheimer’s disease (AD), it has been also reported in subcortical neurodegenerative diseases and vascular lesions. We aimed to investigate the difference between AD, subcortical vascular dementia (SVaD) and mild cognitive impairment (MCI) patients by means of ideomotor limb apraxia frequency and severity. Ninety-six AD, 72 SVaD, and 84 MCI patients were assessed with the mini-mental status examination (MMSe), cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
1
12
1
1
Order By: Relevance
“…In particular, changes in hand functionality may affect the way people communicate or respond to the environment, and interact with objects and tools presented in the surroundings. In neurological diseases associated with aging, such as dementia and Alzheimer's disease, patients may show deficits in performing gestures under verbal command, in imitation or in using common objects (Luchelli, Lopez, Faglioni, & Boller, 1993;Ozkan, Adapinar, Elmaci, & Arslantas, 2013;Rousseaux, Rénier, Anicet, Pasquier, & MackowiakCordoliani, 2012). The praxic performance in these studies is commonly assessed using qualitative measurements and accuracy scales (e.g., Rumiati, Papeo, & Corradi-Dell'Acqua, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, changes in hand functionality may affect the way people communicate or respond to the environment, and interact with objects and tools presented in the surroundings. In neurological diseases associated with aging, such as dementia and Alzheimer's disease, patients may show deficits in performing gestures under verbal command, in imitation or in using common objects (Luchelli, Lopez, Faglioni, & Boller, 1993;Ozkan, Adapinar, Elmaci, & Arslantas, 2013;Rousseaux, Rénier, Anicet, Pasquier, & MackowiakCordoliani, 2012). The praxic performance in these studies is commonly assessed using qualitative measurements and accuracy scales (e.g., Rumiati, Papeo, & Corradi-Dell'Acqua, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Real tool-use impairment prevalence rates were reported with similar levels of 25-54% impaired patients (Del Ser, Hachinski, Merskey & Munoz, 2001;LeClerc, Wells, Sidani, Dawson & Fay, 2004;Wu & Lin, 2015). Moreover, studies indicated that Alzheimer's disease and vascular dementia patients have higher apraxia incidence rates than patients with mild cognitive impairment (Ahmed et al, 2016;Ozkan et al, 2013), frontotemporal dementia (Ahmed et al, 2016;Chandra, Isaac, & Abbas, 2015;Johnen, Frommeyer, et al, 2016;Johnen et al, 2015) or semantic dementia (Baumard et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Further, the incidence rates of apraxia in classic subtests of pantomime and imitation appeared to be on a similar level compared to other test instruments. Other research groups reported prevalence rates of around 28-57% in LHS patients (e.g., Donkervoort et al, 2000;Dovern et al, 2012;Kaya et al, 2006;Weiss et al, 2013) and of 32-69% in Alzheimer s disease patients (Ahmed et al, 2016;Ozkan et al, 2013), but these considered performance in imitation and pantomime tasks only. Had we similarly considered these tasks only (IML, IMF, and PTU), prevalence rates of apraxia for LHS patients would be at 52% for imitation and at 61% for pantomime tasks, which is comparable to previously reported results.…”
Section: Prevalence Rates Of Limb Apraxiamentioning
confidence: 99%
See 2 more Smart Citations